2022
DOI: 10.3390/ph15020223
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Fluorescence Intensity and Antitumor Effect Using Real-Time Imaging in Photoimmunotherapy

Abstract: Photoimmunotherapy (PIT) is a promising tumor-selective treatment method that uses light-absorbing dye-conjugated antibodies and light irradiation. It has been reported that IR700 fluorescence changes with light irradiation. The purpose of this study was to investigate the fluorescence intensity and antitumor effect of PIT using real-time fluorescence observation of tumors and predict the required irradiation dose. The near-infrared camera system LIGHTVISION was used to image IR700 during PIT treatment. IR700 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Takashima et al conducted a study using nine mice in a fluorescence imaging experiment and found that the fluorescence decayed rapidly after irradiation and reached equilibrium between 150 and 330 s, maximizing the anti-tumor effect [ 14 ]. As the present results exhibited similar behavior, the obtained fluorescence images were considered reliable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Takashima et al conducted a study using nine mice in a fluorescence imaging experiment and found that the fluorescence decayed rapidly after irradiation and reached equilibrium between 150 and 330 s, maximizing the anti-tumor effect [ 14 ]. As the present results exhibited similar behavior, the obtained fluorescence images were considered reliable.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research by Sato et al reported that the fluorescence of Cet-IR700 can be observed by NIR light exposure [ 12 , 13 ]. Takashima et al used a fluorescence imaging system (LIGHTVISION, SHIMADZU, Japan) to visualize the real-time drug accumulation of light-sensitive substances in tumors, and they demonstrated a correlation between the decay rate of the fluorescence intensity and the anti-tumor effect [ 14 ]. However, current endoscopes are unable to employ the configuration that is required for fluorescence observation when treatment is performed, especially in the digestive tract.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, 50 J/cm 2 , the light dose at which the intratumor fluorescence disappeared completely, was considered to be the saturation dose in this experiment, and theoretically no improved therapeutic effect is expected by increasing the light dose above this saturation dose. The relationship between fluorescence imaging and therapeutic efficacy in an immunocompromised mouse model using the A431 tumor and Cetuximab has recently been reported [ 23 ]. In the article, the authors concluded that approximately 40 J/cm 2 was the light dose with saturating NIR-PIT therapeutic effects.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research by Sato et al reported that the fluorescence of Cet-IR700 can be observed by NIR light exposure [12,13]. Takashima et al used a fluorescence imaging system (LIGHTVI-SION, SHIMADZU, Japan) to visualize the real-time drug accumulation of light-sensitive substances in tumors, and they demonstrated a correlation between the decay rate of the fluorescence intensity and the anti-tumor effect [14]. However, current endoscopes are unable to employ the configuration that is required for fluorescence observation when treatment is performed, especially in the digestive tract.…”
Section: Introductionmentioning
confidence: 99%